Analysis of The Stability of The Temporary Tunnel Support Structure in The Excavation Phase of The Cipanas Dam Tunnel - Rezeki, Ingrid Multi; prasetyo, singgihangga (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Dams are generally equipped with bypass tunnels. The circumvention tunnel functions to maintain the safety of the dam and can reduce excessive water pressure around the dam. This can help prevent collapse or damage to the dam structure due to excess pressure. The objectives of this research are to determine the implementation of making temporary support structures in tunnels, to obtain the maximum stress values that occur in temporary tunnel support structures, to obtain deformation values that occur in tunnels and safety factors related to the use of steel H Beam as reinforcement, to find out the results of stability analysis. tunnel temporary support structure. Method for analyzing soil stability during the installation of steel supports during the implementation of bypass channel work using the 2D plaxis program approach. The main stress in the Cipanas dam tunnel is tensile stress. The maximum tensile stress occurs at the top of the tunnel due to gravity and groundwater loads. Axial deformation in the Cipanas dam tunnel is deformation that occurs in the direction of the tunnel axis. Maximum axial deformation occurs at the top of the tunnel due to gravity and groundwater loads. Data from stress analysis and deformation analysis at Sta. 0+180.76 total stress -1.56*103kN/m2 relative shear stresses 0.99 deformed mesh 34.84*10-9 m scealead up 100.00*106 total displacement 34.86*10-9 E-mst 1.00, Sta. 0+280.76 total stress -2.82*103kN/m2 relative shear stresses 0.72 deformed mesh 613.16*10-6 m scealead up 10.00*103 total displacement 613.16*10-6 E-mst 1.00, Sta. 0+480.76 total stress -1.61*103kN/m2 relative shear stresses 1.00 deformed mesh 2.19*106 m scealead up 2.00*10-6 total displacement 2.19*106 E-mst 1.938 Keyword: Main Dam, Avoidance Tunnel, Stability.